Chapter Approccio metodologico: costruire per il TDDI - Pantaleo, Liboria (Strumenti per la didattica e la ricerca, 2022)
The TDDI experimentation looks at distance teaching as an educational opportunity for the student strongly anchored to a shared planning with the School Tutor. TDDI is, in part, very close to the concept of E-Learning understood as a teaching and learning methodology capable of involving both the product and the training process. In this perspective, the training product must be understood as any type of content made available in digital format. The training process is referred to the management of the entire teaching process involving all aspects of delivery, fruition, interaction, evaluation.